Range and frequency of AORTIC arch variants in a South African population - Kasirye, Napo Nalunga Sayfa (Division of Radiology, 2020)
The purpose of this study was to describe the range and frequency of aortic arch (AA) branching patterns using multi-detector computed tomography (MDCT). MDCT images of 400 patients who attended Groote Schuur Hospital between January 2013 and December 2014 for CT Chest and CT Thoracic angiogram were assessed. Six different branching patterns were observed. A left-sided AA with three major branches was present in 67% of the patients. Bovine-type AA (26 %) and independent origin of the left vertebral artery (5%) were the next two most common patterns. The pattern and distribution of aortic arch branching patterns demonstrated in our study matches those found in studies conducted in other populations in South Africa, Kenya and other countries around the world. In addition, a link between gender and aortic arch branching patterns has been demonstrated in our study. Knowledge of the presence of variant aortic arch branching patterns will aid interventionists and surgeons to better plan procedures in order to avoid complications. Therefore, performing CT Angiograms of the chest in patients admitted for procedures involving the thorax would be beneficial.